2014
DOI: 10.1891/1058-1243.23.3.155
|View full text |Cite
|
Sign up to set email alerts
|

What Started Your Labor? Responses From Mothers in the Third Pregnancy, Infection, and Nutrition Study

Abstract: Many behaviors and substances have been purported to induce labor. Using data from the Third Pregnancy, Infection, and Nutrition cohort, we focus on 663 women who experienced spontaneous labor. Of the women who reported a specific labor trigger, 32% reported physical activity (usually walking), 24% a clinician-mediated trigger, 19% a natural phenomenon, 14% some other physical trigger (including sexual activity), 12% reported ingesting something, 12% an emotional trigger, and 7% maternal illness. With the exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Based on previous studies that have reported a relationship between fasting and preterm birth or premature rupture of membranes, 9,10,12 we hypothesized that skipping one or more daily meals during pregnancy would result in an immediate, possibly transient, increased likelihood of spontaneous labor within the subsequent 24 hours. None of the individuals in this analysis, when asked an open‐ended question, attributed the onset of their labor to meal patterning, 22 yet we found a strong association. To our knowledge, this is the first study to assess the relationship between meal patterning and imminent likelihood of spontaneous labor at term.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Based on previous studies that have reported a relationship between fasting and preterm birth or premature rupture of membranes, 9,10,12 we hypothesized that skipping one or more daily meals during pregnancy would result in an immediate, possibly transient, increased likelihood of spontaneous labor within the subsequent 24 hours. None of the individuals in this analysis, when asked an open‐ended question, attributed the onset of their labor to meal patterning, 22 yet we found a strong association. To our knowledge, this is the first study to assess the relationship between meal patterning and imminent likelihood of spontaneous labor at term.…”
Section: Discussionmentioning
confidence: 51%
“…If a study participant provided an answer other than one of these, their response was recorded verbatim and later coded by a researcher (AKN) to determine whether they experienced spontaneous onset of labor. The most commonly reported triggers were walking, spontaneous rupture of membranes, and sexual intercourse 22 . The main analysis is limited to those participants who experienced spontaneous onset of labor.…”
Section: Methodsmentioning
confidence: 99%